PENGARUH PERSONAL ATTRIBUTES, ADVERSITY QUOTIENT DENGAN MEDIASI SELF EFFICACY TERHADAP MINAT BERWIRAUSAHA - Astri, Wiwin; Latifah, Lyna (Economic Education Analysis Journal, 2017)
This study aimed to figure out the influence of personal attributes (personality). Adversity quotient and self efficacy towards the students’ entrepreneurial interest of economics faculty of semarang state university. This study was undertaken on 277 students of economics faculty of semarang state university as the samples using propotional random sampling. In addition, the data collection technique used was a questionnaire, then the data were analyzed by path analysis. The results of the study showed that there were 21.7% of the effectof personality towards the entrepreneurial interest, 18% of the effect of adversity quotient toward the student’s entrepreneurial interest, 57% of the effect of self efficacy towards the student’s entrepreneurial interest, 49% of the effect of personality towards the self efficacy, 20.2% of the effect of adversity quotient towards the self efficacy, 27.9% of the effect of personality through self efficacy towards the students’ entrepreneurial interest, and 11.5% of the effect of the effect of adversity quotient through the self efficacy towards the entrepreneurial interest.It can be concluded that there are significant effects of personal attributes (personality) and adversity quotient towards the entrepreneurial interest either directly or indirectly. The researcher suggests that the university students should improve their entrepreneurial spirit by attending training and seminar about entrepreneurship, and the next researcher to examine different objects as well as adding an external variable in accordance with the research.